2016
DOI: 10.1186/s13256-016-0806-x
|View full text |Cite
|
Sign up to set email alerts
|

Invasive urothelial carcinoma, lymphoma-like/plasmacytoid variant, successfully treated by radical cystectomy with adjuvant chemotherapy: a case report

Abstract: BackgroundInvasive urothelial carcinoma, lymphoma-like/plasmacytoid variant, is a rare histological type of bladder cancer similar to plasma cells and is an aggressive variant of urothelial carcinoma associated with a poor prognosis.Case presentationA 41-year-old Asian man was referred to our hospital due to macroscopic hematuria. Cystoscopy detected a non-papillary tumor, and a transurethral resection of the bladder tumor revealed pT1N0M0 bladder cancer. A pathological examination showed high-grade invasive u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…However, the SEER database does not provide information on chemotherapy, which was an obvious weakness of our study. Although some studies found that SRCC was resistant to systematic chemotherapy based on small sample sizes (18), some recent studies reported that adjuvant chemotherapy may be a potential component of effective treatment (21,22). Checkpoint-inhibitor drugs and genomic research offer hope to improve the treatment of bladder cancer (23).…”
Section: Discussionmentioning
confidence: 99%
“…However, the SEER database does not provide information on chemotherapy, which was an obvious weakness of our study. Although some studies found that SRCC was resistant to systematic chemotherapy based on small sample sizes (18), some recent studies reported that adjuvant chemotherapy may be a potential component of effective treatment (21,22). Checkpoint-inhibitor drugs and genomic research offer hope to improve the treatment of bladder cancer (23).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, none of the patients with PUC tested positive for PD-L1, and pembrolizumab was not effective in all patients, except in one. 3,8,11 In the current case, the tumor was negative for PD-L1, and pembrolizumab was not clinically effective for the treatment of the primary tumor. Although active CTCs, which have potential for metastasis, were observed, distant metastasis was not observed during autopsy.…”
Section: Discussionmentioning
confidence: 61%
“…4 Generally, the treatments of local PUC are radical cystectomy and adjuvant chemotherapy, and that of advanced PUC is chemotherapy. 8 Chemotherapy comprises methotrexate, vinblastine, doxorubicin, and cisplatin (M-VAC), or GC is provided to almost all patients with advanced PUC.…”
Section: Discussionmentioning
confidence: 99%
“…38 Acute life-threatening hyponatraemia with seizure and coma has also been reported with vincristine. 42 In a retrospective analysis, Asians were found [46][47][48] Antifungal azoles can inhibit metabolism and worsen hyponatraemia/neurotoxicity 44 Platinum compounds Hyponatraemia 1-2 days • SIADH -unclear mechanism [65][66][67][68] • RSWS -cisplatin-induced renal tubular necrosis [61][62][63][64] • Potent stimulation of ADH by therapy-induced nausea 35 • Overzealous administration of large volumes of hypotonic fluid 51,69 Overzealous co-administration of hypotonic fluid to be avoided Hypernatraemia -• Acquired NDI -reduced expression of AQP2 channels on apical membranes of renal tubules 45,52,70 • Cisplatin-induced hypokalaemia can cause reversible NDI by decreasing AQP2 expression;…”
Section: Vinca Alkaloidsmentioning
confidence: 99%
“…Onset is early, occurring in the first 2 days after administration of cisplatin, and sodium levels normalise rapidly after removal of the offending drug. [65][66][67][68] Other causes…”
Section: Syndrome Of Inappropriate Secretion Of Antidiuretic Hormonementioning
confidence: 99%